Strategi Pengembangan Usaha Keripik Pisang Kecamatan Konda Kabupaten Konawe Selatan - Syarwal, Syarwal; Dirgantoro, Muhammad Arief; Gafaruddin, Abdul (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2018)
The research aims to know the strengths, weaknesses, opportunities, and threats of banana chips development of UD. Sederhana and know the development strategies of banana chips UD.Sederhana.Methods of data analysis used are a descriptive analysis and SWOT analysis. The design of alternative development strategies of banana chips using the SWOT Matrix and Matrix Grand strategy.The results of this research showed that UD. Sederhana used the development strategy of Aggressive Growth Strategy.However, should be done gradually in accordance with the scale of priorities.Based on the priorities of the strategy illustrates that UD. Sederhanais SO (Strengths-Opportunities) strategy. Those are maintaining production quality, affordable prices, expanding the production of banana chips with different input source